PERFORMANCE OF THE CLONAL GARDENS OF THE OLIVE TREE OBTAINED BY CUTTING AND GRAFTS IN SUCCESSIVE CUTS - OLIVEIRA, Adelson Francisco de; NETO, João VIEIRA; VILLA, Fabíola; SILVA, Luiz Fernando de Oliveira da (Scientia Agraria, 2010)
The objective of this work was to evaluate the performance of clonal olive tree gardens in successive cuts at its propagation by cutting. The study was conducted in the Epamig of Maria da Fé, Minas Gerais State, Brazil. The clonal garden was installed in March 2006, in grooves with 40 cm in depth. Two cultivars (Ascolano 315 and Arbequina) were evaluated and cuts in three years (2007, 2008 and 2009). The test was conducted in split plot in time in a randomized block design with five replications. The plots were composed of three lines, spaced between itself in one meter, three plants in each line, 0,5 m of one another, a total of nine plants per plot, being the evaluations carried through in three more vigorous plants. For evaluation, three plants were pruned to 20 cm height of the soil, after 12 months of cultivation, being evaluated the plants height, torso diameter the 20 cm height of the soil, average length of branches, yield of cutting number with four knots by leaves two pairs and total green mass accumulated. In all features evaluated, better results were observed in the ‘Ascolano 315’ by cutting. The successive cuts may be extended for three years higher period.